Characterization of short pineapple leaf fiber reinforced tapioca biopolymer composites - Jamiluddin, Jaafar (2019)
The development of environmental friendly material, such as natural fiber composites, has been getting more attention in recent years due to increase in environmental awareness of various adverse petroleum-based polymer effects. Among all natural fibers, pineapple leaf fiber (PALF) has great potential as a reinforcement agent because it is low cost, highly available with high cellulose content, and has relatively higher mechanical properties as compared to other natural fibers. Most previous research works had used PALF as reinforcement in non-biodegradable petroleum-based polymers to produce natural fiber composites. However, the starch-based polymer innovation, called tapioca biopolymer (TBP), provides an alternative for biodegradable matrix for the development of environmental friendly composites. Therefore, the combination of PALF and TBP in bio-composites development appears to be a perfect balance between the ecology and economic perspectives. As a new combination, this research was conducted to determine the optimum PALF-TBP composites combination parameters to produce competitive mechanical properties. To produce high mechanical properties, there are four essential considerations in the preparation of composites, such as the manufacturing process temperature, fiber length, fiber composition and treatment involved. The experimental work began with material characterization of TBP and PALF. Then, sample preparation was conducted, which consisted of fiber crushing and sieving, internal mixing, hot press and machining. TBP samples at different processing temperatures (160°C, 165°C, 170°C, 175°C, 180°C and 185°C) were prepared to determine the optimum processing temperature. Also, composite samples with different fiber lengths (0.10-0.50 mm, 0.51-1.00 mm and 1.01-2.00 mm) and different fiber loadings (10%, 20%, 30% and 40%) were prepared to evaluate the effect of varying fiber lengths and fiber loadings on mechanical properties of PALF-TBP composites. On the other hand, three different treatments were selected, which were maleic anhydride polypropylene (MAPP) compatibilizer, maleic anhydride polyethylene (MAPE) compatibilizer and alkali treatment for investigating the treatment effect on tensile properties of PALF-TBP composites. The analyses to determine the entire research objective consisted of thermal properties analysis and mechanical properties analysis. In addition, the scanning electron microscopy (SEM) analysis was carried out for result validation. Test results established that the optimum processing temperatures for TBP are 165°C to 170°C with the best combination for the development of short PALF reinforced TBP composite was produced by a hot press process, comprising 30% fiber loading and 7% MAPP coupling agent. However, the influence of various fiber lengths of up to 2.00 mm provided no significant influence on the production of maximum tensile properties. The finding demonstrated that the combination of short PALF and TBP had great potential as environmental friendly composites to be an alternative for the conventional polymers in engineering applications, especially in the automotive sector. Improvement of future PALF-TBP composites development, such as the utilization of PALF with higher tensile strength, is expected to be capable of enhancing and improving the present result.